Historical analysis of materials used in Iranian paper dyeing with special reference to the effect of henna dye on paper based on scientific analysis - Barkeshli, Mandana; Ataie, Ghasem; Alimohammadi, Mahmood (2008)
During the Taimurid and Safawid periods the masters introduced a number of dyes for coloring paper for the purpose of calligraphy and paintings. Historical analysis was carried out to identify different dyes, shade of colors, and the application of techniques recommended in the paperdyeing process based on Persian historical treatises. Among the many dyes introduced by the masters, henna has been the most recommended, with a ratio of 1:10 henna and water. Scientific analysis was carried out in two stages to investigate the effect of henna on paper in a lower concentration than the advised ratio, followed by laboratory work to investigate the fungicidal properties of henna dye in the advised concentration. Our experiment showed that henna acts as a fungicide on aspergillus flavus only when the ratio of henna to water is higher than 1:10. The present study revealed the secret behind the henna concentration that has been stressed in historical recipes.